2009
DOI: 10.4103/0022-3859.52842
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for female sexual dysfunction in women attending a medical clinic in south India

Abstract: Sexual problems suggestive of dysfunction, as suggested by FSFI total and domain scores, are highly prevalent in the clinic setting, particularly among women above 40 and those less educated, but confirmation using locally validated cut-off scores of the FSFI is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
8
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 37 publications
7
80
8
8
Order By: Relevance
“…La mayor prevalencia de DSF, se presentó en mujeres hindúes, debido posiblemente a la cultura y a la imposibilidad que tiene la mujer para tener acceso a una evaluación acerca de su sexualidad (15). Infortunadamente, el cuestionario FSFI no fue validado en esta población, lo que podría llevar a un posible sesgo de información de los resultados obtenidos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La mayor prevalencia de DSF, se presentó en mujeres hindúes, debido posiblemente a la cultura y a la imposibilidad que tiene la mujer para tener acceso a una evaluación acerca de su sexualidad (15). Infortunadamente, el cuestionario FSFI no fue validado en esta población, lo que podría llevar a un posible sesgo de información de los resultados obtenidos.…”
Section: Discussionunclassified
“…La presencia de enfermedad médica de base (6,11,18), la presencia de bajo nivel educativo (6), tener solo educación primaria (16) y secundaria (13,15), demostraron ser un factor de riesgo significativo para presentar DS, mientras que ésta no se encontró asociación con las personas que habían recibido algún tipo de educación adicional (11) (Tabla V).…”
Section: Tabla II Descripción Y Criterios De Calidad De Los Estudios unclassified
“…It further showed a high rate of hesitancy in seeking help because of economic and sociocultural considerations [2]. Numerous studies from diverse geographic and sociocultural backgrounds have suggested similar problems globally [1, 3, 4, 5, 6, 7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…It has also been used to evaluate sexual problems in adolescence, pregnancy, middle and menopausal ages [5, 6, 24, 25]. It has been used to evaluate sexual problems in various clinical conditions, like women with diabetes mellitus, hypertension, female genital mutilation, obstructive sleep apnea, medical tinnitus, spinal cord injury, pelvic surgery, elective aortic surgery, and women from a medical clinic [7, 26, 27, 28, 29, 30, 31, 32, 33, 34]. …”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of information about female sexual dysfunctions in India. The FSFI score used to study this dysfunction has to be individualised as it is standardized in west so reports very high score when applied on Indian population (26,27,28) . In study of our country we have to take into account our cultures, social structure and status of women here and give due consideration to these factors.…”
Section: Discussionmentioning
confidence: 99%